HISTORICAL PERSPECTIVES OF FISHERIES RESEARCH AND DEVELOPMENT IN INTEGRATED WATERSHED MANAGEMENT - Muruganandam, M.; Samra, J.S. (Journal of Soil and Water Conservation, 2022)
Fish hunting and fanning have a very long history from as early as teed ages, but their contribution in watershed management programmes started only iii the recent past. Both fish farming and watershed management have hnnlenSe potential as well as challenges for sustainable development that need to be harnessed through resource optimisation. It is in this situation, a retrospect analysis was carried out reviewing the historical development of fisheries research and management in general and in the perspectives of watershed management programmes. The analysis revealed that fisheries management interventions in watershed programmes are very recent and it requires a strategic plan to match the demand-supply and resource generation-exploitation. This paper details the evolutionary status and figure thrusts for the active development of fisheries in watershed management efforts towards establishing resource and knowledge based prosperity.